The multiple roles of exosomes in Parkinson's disease: an overview. (4th July 2019) - Porro, Chiara; Panaro, Maria Antonietta; Lofrumento, Dario Domenico; Hasalla, Elona; Trotta, Teresa
Abstract: The extracellular vesicles (EVs) represent a relatively new field of research in neurodegenerative disease and they are thought to be one of the ways that neurodegenerative pathologies, such as Parkinson's Disease (PD), spread in the brain. EVs are membrane vesicles released from cells into the extracellular space and they are produced by all cells of the nervous tissue. The classification of the vesicle subtypes comprises exosomes, microvesicles/microparticles, apoptotic bodies. EVs change in number and content in response to environmental conditions and may function as shuttles for the delivery of cargo between cells. Recent data suggest that exosomes secreted by both activated microglia and neurons play an important role in α-synuclein (α-syn) spreading and increase of neuroinflammation, thus exacerbating neuronal dysfunction and disease progression. α-syn is a presynaptic protein secreted by neurons in small amounts, and it is the main component of Lewy bodies, one of the histopathological features of PD. Several factors have shown to induce and/or modulate α-syn structure and oligomerization in vitro . Under pathological conditions, progressive accumulation of α-syn and the formation of oligomers have been proposed to play a critical role in the pathogenesis of PD. This review gives an overview about the multiple roles of exosomes in PD, despite their role in the progression of neurodegeneration, exosomes could represent a specific drug delivery tool for a difficult target such as the brain, which poses an obstacle to most drugs and they could also represent new biomarkers to track the progression of PD.